Penerbitan Kartu Keluarga Bagi Pasangan Nikah Siri Dan Akibat Hukumnya Terhadap Para Pihak - Alif Utama, Daffa; Pujiastuti, Endah; Septiandani, Dian (Universitas Semarang, 2022)
The purpose of this study is to determine the issuance of family cards for unregistered married couples, as well as the legal consequences of issuing family cards for unregistered married couples from the perspective of state administrative law. In marriage law, unregistered marriage is an unregistered marriage, often only fulfilling the pillars and requirements for a valid marriage according to the Islamic religion, but from a legal point of view it has no juridical power, especially for his wife and children later. One of the Government's breakthroughs related to unregistered marriages is the policy of issuing family cards for unregistered married couples. This policy is a positive step in the context of providing equal protection and rights for citizens, but other problems also accompany the presence of this policy. This research article reviews the issuance of family cards for unregistered married couples and the legal consequences of issuing family cards for unregistered married couples from the perspective of state administrative law. This research is normative legal research with a statutory approach. The results of this study, several additional requirements must be met for unregistered married couples to apply for the issuance of a family card. If the family card has been issued, it is also possible to have administrative impacts on children, wives, and husbands related to population administration. Tujuan dari penelitian ini untuk menganalisis penerbitan kartu keluarga bagi pasangan kawin siri, serta akibat hukum dari penerbitan kartu keluarga bagi pasangan nikah siri dalam perspektif hukum administrasi negara. Dalam hukum perkawinan, kawin siri merupakan perkawinan tidak tercatat, seringkali hanya memenuhi rukun dan syarat sahnya perkawinan menurut agama Islam, namun dari sisi hukum tidak memiliki kekuatan yuridis, terlebih untuk istri dan anaknya nanti. Salah satu terobosan pemerintah terkait dengan perkawinan siri adalah kebijakan penerbitan kartu keluarga bagi pasangan nikah siri. Kebijakan ini merupakan langkah positif dalam konteks memberikan perlindungan dan hak yang sama bagi warga negara namun problematika lain turut menyertai hadirnya kebijakan tersebut. Artikel hasil penelitian ini mengulas tentang penerbitan kartu keluarga bagi pasangan kawin siri dan akibat hukum penerbitan kartu keluarga bagi pasangan kawin siri dalam perspektif hukum administrasi negara. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan. Hasil penelitian ini, terdapat beberapa syarat tambahan yang harus dipenuhi bagi pasangan nikah siri untuk mengajukan permohonan penerbitan kartu keluarga. Apabila kartu keluarga sudah terbit, dimungkinkan pula timbul dampak secara administratif terhadap anak, istri, maupun suami berkaitan dengan adminitrasi kependudukan.